circIQCH sponges miR-145 to promote breast cancer progression by upregulating DNMT3A expression - Li, Yuehua (Aging (Albany NY), 2020)
As a unique type of RNA, circular RNAs (circRNAs) are important regulators of multiple biological processes in the progression of cancer. However, the potential role of most circRNAs in breast cancer lung metastasis is still unknown. In this study, we characterized and further investigated circIQCH (hsa_circ_0104345) by analyzing the circRNA microarray profiling in our previous study. circIQCH was upregulated in breast cancer tissues, especially in the metastatic sites. CCK-8, transwell, wound-healing and mouse xenograft assays were carried out to investigate the functions of circIQCH. Knockdown of circIQCH inhibited breast cancer cell proliferation and migration to lung. Moreover, luciferase reporter assays and RNA immunoprecipitation assays were performed to elucidate the underlying molecular mechanism of circIQCH. The results showed that circIQCH sponges miR-145 and promotes breast cancer progression by upregulating DNMT3A. In summary, our study demonstrated the pivotal role of circIQCH-miR-145-DNMT3A axis in breast cancer growth and metastasis via the mechanism of competing endogenous RNAs. Thus, circIQCH could be a potential therapeutic target for breast cancer.